2008
DOI: 10.1111/j.1365-2621.2008.01739.x
|View full text |Cite
|
Sign up to set email alerts
|

Cooking DNA: the effect of ‘domestic’ cooking methods on detection of GM potato

Abstract: The ability to detect GM material in otherwise unprocessed foods cooked using domestic methods is important should 'ready-to-eat' foods require labelling. This study addresses the issue of DNA degradation in foods as a result of cooking. A number of 'domestic' cooking methods were shown to affect the length of DNA sequences able to be PCR amplified from potato samples and the degree of degradation was treatmentspecific. However, a. real-time PCR assay was developed and. GM material was positively identified in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…From the available literature, it is known that raw and processed meat products contain in their cellular structure both nuclei and nucleic acids that have not been degraded by either aging or tenderization processes occurring in the meat after animal death (Adjei et al 1995) or thermal and culinary treatment. Until now, it has been found that boiling at elevated and atmospheric pressure, frying in deep fat, or microwave treatment retains DNA fragments of plant (Van Der Colff and Podivinsky 2008) or animal origin (Arslan et al 2006) of sufficient quality and quantity to enable amplification of these fragments with polymerase chain reaction (PCR) techniques. This applies to experiments on both identification of species and amplification of fragments encoding particular proteins, specific to a source material.…”
Section: Introductionmentioning
confidence: 99%
“…From the available literature, it is known that raw and processed meat products contain in their cellular structure both nuclei and nucleic acids that have not been degraded by either aging or tenderization processes occurring in the meat after animal death (Adjei et al 1995) or thermal and culinary treatment. Until now, it has been found that boiling at elevated and atmospheric pressure, frying in deep fat, or microwave treatment retains DNA fragments of plant (Van Der Colff and Podivinsky 2008) or animal origin (Arslan et al 2006) of sufficient quality and quantity to enable amplification of these fragments with polymerase chain reaction (PCR) techniques. This applies to experiments on both identification of species and amplification of fragments encoding particular proteins, specific to a source material.…”
Section: Introductionmentioning
confidence: 99%
“…, 2008), as well as the carbohydrate based research of Fernando et al. (2008), Ikhu‐Omoregbe & Bushi (2008) and van der Colff & Podivinsky (2008).…”
mentioning
confidence: 99%